Influence Annealing on the Physical Properties of Silver Selenide Thin Film at Different Temperatures by Thermal Evaporation - Mumtaz, Hiba; I. H. Khudayer (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2023)
This survey investigates the thermal evaporation of Ag2Se on glass substrates at various thermal annealing temperatures (300, 348, 398, and 448) °K. To ascertain the effect of annealing temperature on the structural, surface morphology, and optical properties of Ag2Se films, investigations and research were carried out. The crystal structure of the film was described by Xray diffraction and other methods.The physical structure and characteristics of the Ag2Se thin films were examined using X-ray and atomic force microscopy (AFM) based techniques. The Ag2Se films surface morphology was examined by AFM techniques; the investigation gave average diameter, surface roughness, and grain size mutation values with increasing annealing temperature (75.74 nm–96.36 nm). Additionally, With various variations to the nominal values, the absorbance and transmittance spectra are further studied and reported in accordance with the wavelength range of (400-1100) nm. The findings indicate that the sample highest absorbance value was attained at a temperature treatment of 448 K, whereas the sample highest transmittance was at a temperature treatment of 300 K. According to the results, direct transitions were permitted in the under-review thin films at optical energies of (2.15, 1.85, 1.75, and 1.7) eV, respectively